Spontaneous rupture of sac in bochdalek hernia leading to acute intestinal obstruction - Vidyanand P Deshpande; Rajgopal J Totla; Arjun A Pawar; Pravin R Suryawanshi (Wolters Kluwer Medknow Publications, 2021)
Bochdalek hernia usually presents in neonates in the form of respiratory distress. Presentation as acute intestinal obstruction is extremely rare. We report a 6-month-old male infant with spontaneous rupture of the sac in a Bochdalek hernia leading to acute gastrointestinal obstruction. Diaphragmatic hernia can rarely present as acute intestinal obstruction due to spontaneous rupture of sac.